2014
DOI: 10.2741/4200
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of mesenchymal stromal cells in lymphoproliferative disorders

Abstract: Accumulating evidence indicates that bone marrow microenvironment plays an important role in the pathogenesis of some myeloid and lymphoid hematological malignancies (HM). Among different environmental associated parameters, those related to functional, cytogenetic and immunological integrity of mesenchymal stromal cells (MSC) are particularly relevant. Functional alterations and immunophenotypic abnormalities have been described in MSC obtained from HM patients. These data seem to confirm the defective biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…28 MSCs are present in the BM stroma to provide microenvironmental support to HPCs with whom they share an ontogenic link. 29,30 Despite MSCs sharing cytogenetic alterations with HPCs in MPN, MDS, and other hematologic disorders, [31][32][33][34] no study has been reported so far in which the presence of the KIT D816V mutation is investigated in BM MSCs from ISM patients.…”
Section: Introductionmentioning
confidence: 99%
“…28 MSCs are present in the BM stroma to provide microenvironmental support to HPCs with whom they share an ontogenic link. 29,30 Despite MSCs sharing cytogenetic alterations with HPCs in MPN, MDS, and other hematologic disorders, [31][32][33][34] no study has been reported so far in which the presence of the KIT D816V mutation is investigated in BM MSCs from ISM patients.…”
Section: Introductionmentioning
confidence: 99%